101A SEMANTICS ANALYSIS OF IDIOMATIC EXPRESSION IN CRUELLA FILM - Jannah, Nurul; Oktariza, Dodi; Efendi, Dedi (Universitas Muara Bungo, 2023)
The research analyzes the types of idiomatic expressions and how the classification of the meaning of idiomatic expressions found in Cruella film. The objectives of this research are (1) to find the types of idiomatic expressions, and (2) to explain the classification meaning of idiomatic expressions found in Cruella film. The writer used the descriptive qualitative method because this research aimed to describe the meaning of an idiom from utterances on film spoken by characters. The process of analysis used Lim’s theory (2004) which explains the six types of idiomatic expressions. The classification of meaning from the idiomatic expressions refers to seven types of meaning supported by Leech (1981).The result of the research reveals some findings. There are 83 data the writer collects from utterances spoken by characters in Cruella film, 37 phrasal verbs with percentage of 44.57%, 4 prepositional phrases with 4.81%, 13 idioms with verbs as keywords with 15.66%, 8 idioms with nouns as keywords with 9.63%, 18 idioms with an adjective as keywords with 21.68%, and 3 idiomatic pairs with 3.61%. The writer also often finds repetition of idiomatic expressions in Cruella film, especially phrasal verbs. Moreover, the writer also classify into four from seven types of meaning, conceptual meaning 45.78% with 38 data, connotative meaning 26.50% with 22 data, affective meaning 9.63% with 8 data, and collocative meaning 18% with 15 data. The writer hope that the research can make the readers know more about idioms. By understanding of idiomatic expressions, the writer hopes that readers can improve their language skills like native speakers. The writer suggests future researchers improve the next writer can be able to be deep again in studying idiomatic expressions.